Inflammation-Specific T Imaging Using Anti-Intercellular Adhesion Molecule 1 Antibody-Conjugated Gadolinium Diethylenetriaminepentaacetic Acid - Kyu-Sil Choi; Sun-Hee Kim; Quan-Yu Cai; Soo-Yeon Kim; Hyang-Ok Kim; Hye-Jin Lee; Eun-A Kim; Seong-Eon Yoon; Ki-Jung Yun; Kwon-Ha Yoon (Molecular Imaging)
To examine inflammatory tissue, an initial and common symptom of various types of pathogenesis, we designed inflammation-targeted T 1 contrast agents prepared by bioconjugation of gadolinium diethylenetriaminepentaacetic acid (Gd-DTPA) with anti-intercellular adhesion molecule 1 (ICAM-1) antibody. The anti-ICAM-1 antibody was coupled with DTPA and was then conjugated with Gd. The specific binding of the Gd-DTPA-anti-ICAM-1 antibody complex to the ICAM-1-expressing cells was examined in the cultured endothelial cells where ICAM-1 expression was stimulated. Inflammation-specific T 1 imaging was then assessed using a mouse abscess model with the 1.5-Tesla module. The Gd-DTPA-anti-ICAM-1 antibody displayed increased r1, which was two times higher than that of Gd-DTPA and showed predominant binding to cultured endothelial cells, which expressed a high level of ICAM-1. Moreover, the inflammation-specific T 1 enhancement was imaged with the Gd-DTPA-anti-ICAM-1 antibody in the mouse acute inflammation model. The Gd-DTPA-anti-ICAM-1 antibody showed significantly increased vascular circulation time, which thereby offered a greater chance for its binding to the target cells. The Gd-DTPA-anti-ICAM-1 antibody displays a potential targeted T 1 contrast agent specific to the inflammatory tissue that expresses ICAM-1.